Relevance of Critical Pedagogy to Accountancy and Business Studies Education in Schools - Wadhwa, Toolika (JOURNAL OF INDIAN EDUCATION, 2016)
Education in accountancy and business studies at the senior secondary level in schools has long been criticised for emphasising on materialism and monetary success with little or no emphasis on ethical considerations and humanistic values. The dominance of capitalistic values in education in the commerce stream has highlighted the need for a critical perspective to the curriculum of commerce. This paper revisits education in accountancy and business studies from the perspective of critical pedagogy, drawing upon the works of Henry Giroux. Further, it explores the potential in commerce education to develop critical thinking in students.